Gut commensal bacteria influence colorectal cancer development by modulating immune response in AOM/DSS-treated mice - Danlei Zhou; Yujing Sun; Peipei Ding; Xiaochao Wang; Ling Li; Luying Li; Xinyue Lv; Tian Liao; Jianfeng Chen; Wei Zhang; Qi Wang; Qing-Hai Ji; et al. (Microbiology Spectrum)
ABSTRACT The gut microbiota has been closely associated with the pathogenesis of colorectal cancer (CRC). However, precise identification of particular microorganisms promoting CRC carcinogenesis, and more importantly those blocking tumor development, has been challenging based on human gut microbiota profiling studies. With a well-established azoxymethane/dextran sodium sulfate induction murine CRC model, we found a subset of mice consistently failed to develop CRC. This genetically homogeneous but cancer-refractory population gave us a unique opportunity to reveal that the microbial compositions between mice with and without CRC formation are indeed distinct, indicating key different gut microbiota between those groups are responsible for the differential susceptibility of the animals to CRC development. Our analysis revealed that Ruminococcus flavefaciens (R.f) and Fibrobacter succinogenes (F.s) were significantly enriched in CRC-free mice, while the presence of Eubacterium dolichum (E.d) was dramatically reduced. The correlative evidence was further substantiated as important causal factors, with subsequent bacteria intragastric administration experiments demonstrating independent, protective roles of R.f and F.s and a correspondingly detrimental role of E.d in inflammation-induced CRC initiation. Notably, E.d strongly activates NF-κB and promotes the local accumulation of myeloid-derived suppressor cells and macrophages. Significant disturbance of gut immune homeostasis, therefore, might be a critical trigger leading to subsequent CRC development. These findings indicate a clear direction for precise and rational gut microbiota-mediated CRC prevention.IMPORTANCEThere is a complex ecosystem of different microbes residing within the gut, which is highly relevant to health and diseases. The causal linkage between specific gut microbes and the development of colorectal cancer has been established with a mouse model, pinpointing specific bacteria species either promoting or preventing colorectal cancer development. A key aspect of these gut residual bacteria in colorectal cancer development is through exaggerating or easing gut inflammation. Therefore, by taking probiotics composed of corresponding cancer-preventing bacteria from human microbiota, it can be an effective and economic way to reduce human colorectal cancer risks.